Monocytosis as a Prognostic Factor in Idiopathic Pulmonary Fibrosis - Haider, Waseem; Ali Sajjad, Malik Istikhar; Abbas, Muhammad Naveed; Khalid, Usman; Saif ur Rahman; Aqil, Mehvish (Indus Journal of Bioscience Research, 2025)
Objective: To determine increased monocyte, count (monocytosis) as a cellular biomarker for poor outcomes in idiopathic pulmonary fibrosis METHODS: A descriptive cross-sectional study was conducted at Allied Hospital-2, Faisalabad. A total of 305 patients aged 30–70 years with confirmed IPF were enrolled using non-probability consecutive sampling. Monocyte counts were classified into three groups: Group I (<0.60 × 10⁹/L), Group II (0.60–<0.95 × 10⁹/L), and Group III (≥0.95 × 10⁹/L). The primary outcome was in-hospital all-cause mortality. RESULTS: The mean age was 50.6 ± 12.2 years; 53.1% were female. Mortality was significantly higher in Group III (48.6%) compared to Group I (2.9%) and Group II (48.6%) (p = 0.017). Stratified analysis revealed consistent trends, with statistically significant associations in non-smokers (p = 0.048), non-diabetics (p = 0.035), non-MI patients (p = 0.020), and hypertensive patients (p = 0.041). Elevated monocyte count was a strong predictor of poor outcomes across subgroups. CONCLUSION: Elevated monocyte count, particularly ≥0.95 × 10⁹/L, is associated with increased in-hospital mortality in IPF. Given its accessibility and cost-effectiveness, monocyte count can be used as a prognostic tool for risk stratification and early clinical decision-making.